La retouche des peintures acryliques en émulsion non vernies : Aquazol 200. Étude des capacités physiques, chimiques et optiques d’un liant - Alice Sautois (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Glossy retouching is one of the restoration problems which occur with unvarnished  acrylic emulsion paintings. Due to the sensitivity to many solvents, every glossy retouching technique has to be avoided because they are not compatible.  These investigations have compared the optical abilities of a few water-soluble polymers mixed with water and pigments. The optical feature, the stability and the compatibility of Aquazol 200 have been more deeply evaluated in a scientific way.